A higher percentage of leukemic blasts with vacuoles predicts unfavorable outcomes in patients with acute myeloid leukemia. (October 2021) - Song, Juanjuan; Shang, Baojun; Pei, Yanru; Shi, Mingyue; Niu, Xiaona; Dou, Liurui; Drokow, Emmanuel Kwateng; Xu, Fangfang; Bai, Yanliang; Sun, Kai
Highlights: Blast cell vacuoles could be used as a poor morphological feature of acute myeloid leukemia. A higher percentage of leukemic blasts with vacuoles was associated with adverse genetic features and predicted inferior treatment response and survival. The precise stratification on the percentage of leukemic blasts with vacuoles complemented to current risk classification in AML. Abstract: Cytoplasmic vacuoles, which are a morphological feature of dysplasia, can be observed under a microscope at initial diagnosis. Recently, this typical morphological feature has been found to be associated with impaired survival. To investigate the clinical significance of the grading of blasts with vacuoles in acute myeloid leukemia (AML), we retrospectively studied 152 patients newly diagnosed with non-M3 AML. The patients were categorized into three groups according to the percentage of blasts with vacuoles (>20 %, 11–20 %, 0–10 %). A high percentage of blasts with vacuoles (>20 %) was positively associated with the European Leukemia Net (2017-ELN) high-risk AML, a complex karyotype, TP53 and IDH1/2 mutations, and CD71 expression and negatively associated with the ELN low-risk category. Importantly, patients who had a higher percentage of blasts with vacuoles had a lower complete remission rate in response to first-cycle induction chemotherapy. The overall survival and event-free survival of patients who had a higher percentage of blasts with vacuoles were significantly shorter. Moreover, multivariate analysis showed that blast vacuolization was an independent high prognostic factor for AML. In conclusion, a higher percentage of leukemic blasts with vacuoles predicts worse outcomes in AML and may have potential as a prognostic marker.